Melhoramento cognitivo e pessoalidade : a ética do uso das smart pills - Isabela Cristina Passos e Possas (2019)
Our research has focused on human personhood in the context of smart pills’ development and use. The objective was to discuss the dynamics of these pills’ use in contemporary western culture guided by the set of values which Taylor (1991) called "Ethics of Authenticity." In this context, governed mainly by liberal capitalist society models, production (of goods or knowledge) and profit are valued. Individuals who constitute such societies are always under the influence of these productivist values, and although they may reflectly choose to go against prevailing values, a majority seems to agree with them. By adopting life plans that aim for individual academic, professional, and financial success, people are constantly in competition against each other. Succeeding is often conditioned by the failure of others. We must be better; we have to be extraordinary to be what we want to be. In this context, then, smart pills appear as an output to ordinary performance. Initially produced for therapy of nervous system disabilities such as Attention Deficit Hyperactivity Disorder, these substances have been increasingly sought for improvement purposes after the discovery that they also have a potentiating effect on healthy people. Featuring theories about the development of human personhood and neuroscience concepts to explain what cognition and cognitive treatments/enhancements consist of, we move our research into the field of neuroethics to finally discuss the ethics of using smart pills. We talk about the issues of risk, justice, identity and authenticity. Based on Taylor's (1985b) conception of the person as a self-interpreting animal, we conclude that the increased use of smart pills can be both a form of self-determination and self- fulfillment of people of our time and a symptom of social pressure that has imposed productivity values on our own lives. The reflection that remains is how these values have guided us in the contemporary context and how it is possible to revise them and, from the examination of our culture, continue to give assent to them or transform them.